Legal Analysis of Consumer Protection in E-Commerce Transactions Based on Contract Law and Law Number 8 of 1999 on Consumer Protection - Sarles Gultom; Parlin Dony Sipayung; Yuspika Yuliana Purba; Natalia Ginting (KOLABORASI: Journal of Multidisciplinary, 2025)
Legal protection for consumers in electronic transactions, as regulated in Article 1 paragraph 1 of Law No. 8 of 1999 concerning Consumer Protection which states that "Consumer protection is all efforts that guarantee legal certainty to provide protection to consumers", in transactions that usually use paper-based economy, but in E-Commerce transactions changing into digital electronic economy, special handling is needed from a legal perspective. Review of E-Commerce transactions viewed from a legal perspective, especially those regulated in Article 1320 of the Civil Code, is based on the legal power possessed by consumers in making transactions. This thesis analyzes the legal protection obtained by consumers in making transactions on electronic media. The research method used in this study is a normative legal library research method, namely research that refers to legal norms contained in laws and regulations, literature, expert opinions, and scientific journals. This research is expected to provide benefits both scientifically, namely in the study of legal science, and practically and academically, namely as input for authors and parties who wish to analyze the legal protection that arises in electronic transactions and regarding the validity of electronic contracts.